Integrative analysis of single nucleotide polymorphism of PDE7B (rs2327669) with biopsychosocial and biochemical parameters in β-thalassemia major patients in Pakistani Cohort - Faiza Usmani; Muhammad Zohaib Yaseen; Arshi Ali; Mahrukh Nasir; Saifullah (Molecular Biology Reports, 2026)

Seismic and petrophysical evaluation of the Paleocene Lockhart Formation as a fractured carbonate reservoir in the upper Indus Basin, Pakistan - Muhammad Nauman Ejaz; Hua-Wei Zhou; Zohaib Naseer (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Comparative immune response and disease resistance against Aeromonas hydrophila in Catla catla, Labeo rohita and their intergeneric hybrids - Muhammad Ahmad; Amina Zuberi; Muhammad Noorullah; Zohaib Noor; Waqar Younas; Ajmal Hussain; Muhammad Uzair; Muhammad Kamran (Fish & Shellfish Immunology, 2026)

Toward a Vaccine Against Multidrug-Resistant Elizabethkingia anophelis: Comprehensive Immunoinformatics-Based Design of a Multi-Epitope Vaccine and mRNA Construct - Muhammad Hanzala; Rana Zohaib Abbas; Mahnoor Habib; Allah Rakha Yaseen; Muhammad Suleman; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani; Sehrish Firyal (Probiotics and Antimicrobial Proteins, 2026)

Revisiting the Thornthwaite-Mather method to characterize drought impacts on groundwater recharge in Greece - Muhammad Zohaib; Stavros Stathopoulos; Amirhossein Ahrari; Ali Torabi Haghighi; Konstantinos Kourtidis; Alexandra Gemitzi (Hydrological Sciences Journal, 2026)

Phylogeny and diversity study in Damani sheep through mitochondrial DNA D-loop nucleotides sequence - Muhammad Zohaib; Farhad Ali; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tariq Zeb; Ihsan Ali; Mohammad Qasim; Khalid Khan; Iftikhar Ahmad; Ijaz Ahmad (Tropical Animal Health and Production, 2026)

Theoretical Investigation of Optoelectronic and Photophysical Properties in the Carbazole-based Molecules via DFT and TD-DFT Methodology - Muhammad Zohaib Sabir; Sania Ismaeel; Yasir Ali; Aneeqa Kanwal; Umme Habibah Siddiqua (Journal of Fluorescence, 2026)

Retraction notice to “Discovery of putative inhibitors of human Pkd1 enzyme: Molecular docking, dynamics and simulation, QSAR, and MM/GBSA” [Environ. Res. 257 (2024) 119336] - Muhammad Zohaib Nawaz; Hafiz Rameez Khalid; Sabeen Shahbaz; Khalid A. Al-Ghanim; Arivalagan Pugazhendhi; Daochen Zhu (Environmental Research, 2026)

Sewage Sludge-Mediated Microplastic Transfer to Agroecosystem: A Comprehensive Review on Detection, Fate and Ecological Impacts - Muhammad Tariq Khan; Masroor Waliullah; Zohaib Abbas; Saba Hafeez; Mohammad Bhuyan; Nasrin Akhter; Iqbal Ahmad; Asim Nawab; Mushtaq Ahmad; Yanbo Zhou; Md Faysal Hossain (Water, Air, & Soil Pollution, 2026)
Microplastic (MP) pollution has become a significant environmental concern due to its persistent nature and toxic environmental effects. MPs pose threats to the aquatic and terrestrial environment by impacting plant habitats and altering soil properties. Wastewater treatment plants (WWTPs) are one of the most prominent channels for MP pollution in both aquatic and terrestrial ecosystems. MP particles separated during various treatment processes are trapped in the sludge and subsequently enter the terrestrial agroecosystem when sludge is used as fertilizer. In addition, sludge incineration releases tiny MP particles into the atmosphere. Although MPs have been extensively studied in aquatic environments, limited studies are available regarding their transport to agricultural ecosystems and the pathways through which they pose risk to food security and soil fertility. This review aims to evaluate the prevalence of MPs within sewage sludge and their subsequent translocation into terrestrial agroecosystems. A critical investigation has been carried out to address the challenges in detecting MPs in complex sludge samples to provide guidance for developing standardized and widely accepted methodologies. Furthermore, the impacts of MPs on soil fertility and biota were assessed and investigated from the perspective of agricultural production. This review aims to compile evidence of the presence and transport of MPs through sewage sludge applied to agricultural lands and help policymakers and environmentalists in developing viable strategies to protect agricultural land from MP pollution. Graphical Abstract

RAFE-net: A robust attention-based fusion framework for classifying fish feeding behavior from sonar and acoustic data - Usama Iqbal; Daoliang Li; Muhammad Farrukh Qureshi; Zohaib Mushtaq; Hafiz Abbad Ur Rehman (Aquacultural Engineering, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

Integrating Conventional and machine learning approaches with seismic inversion for optimized porosity estimation in heterogeneous siliciclastic rocks - Muyyassar Hussain; Urooj Shakir; Zohaib Naseer; Muhammad Raiees Amjad; Farooq Arshad; Muhammad Kamal; Ahmed E. Radwan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Machine learning-based dual-parameter inversion for estimating snowpack liquid water content and density using common offset GPR data - Zohaib Akbar; Yuanjun Jiang; Ryan Webb; Anja Klotzsche; Yuanjia Zhu; Aftab Anwar; Muhammad Mudassar Rehman (Science China Earth Sciences, 2026)

An integrated geohazard assessment approach for sustainable small hydropower projects: A case study from the Western Himalayan Syntaxes, Northern Pakistan - Khan Zada; Shengwen Qi; Yongchao Li; Weiwei Zhu; Zan Wang; Bowen Zheng; Songfeng Guo; Muhammad Faisal Waqar; Syed Zohaib Hassan Bukhari (Bulletin of Engineering Geology and the Environment, 2026)

Comparative Transcriptomics of Two Contrasting Cultivars and Functional Verification of HcWRKY70 for Salt Tolerance in Kenaf (Hibiscus Cannabinus L.) - Muhammad Zohaib Afzal; Shurong Gao; Ting Liu; Faxuan Wu; Huawei Wei; Liwu Zhang (Tropical Plant Biology, 2025)

Utilization of physicochemical approach to propose a strategy for biofilm inhibition - Ajab Khan; Muhammad Aasim; Noor Shad Bibi; Haris Saddique; Hizb Ullah; Zohaib Khan; Umar Aziz; Nadir Zaman Khan; Waqar Ali; Noor Muhammad (Biofouling, 2025)

LightHybridNet-Transformer-FFIA: A hybrid Transformer based deep learning model for enhanced fish feeding intensity classification - Usama Iqbal; Daoliang Li; Muhammad Farrukh Qureshi; Zohaib Mushtaq; Hafiz Abbad ur Rehman (Aquacultural Engineering, 2025)

Geothermal investigation of sandstone reservoirs using a probabilistic neural network with 2D seismic and borehole data: insights into structural and reservoir characteristics - Zohaib Naseer; Muhsan Ehsan; Muhammad Ali; Kamal Abdelrahman; Yasir Bashir (Geothermics, 2025)

Micro and Nanoplastics in Ecosystems: Interrelated Sources, Risks, Pathways, Consequences, Mitigation, Challenges and Future Recommendations - Tauqeer Hussain; Muhammad Summer; Shaukat Ali; Rana Rashad Mahmood Khan; Muhammad Pervaiz; Zohaib Saeed (Water, Air, & Soil Pollution, 2025)

An integrated comprehensive approach describing structural features and comparative petrophysical analysis between conventional and machine learning tools to characterize carbonate reservoir: A case study from Upper Indus Basin, Pakistan - Zohaib Naseer; Urooj Shakir; Muyyassar Hussain; Qazi Adnan Ahmad; Kamal Abdelrahman; Muhammad Fahad Mahmood; Mohammed S. Fnais; Muhsan Ehsan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Elicitation of Withania somnifera adventitious roots: in-vitro cultures for enhanced secondary metabolites synthesis - Muhammad Adil; Zohaib Younas; Ilyas Ahmad; Khalid M. Al Rohily; Zia-ur-Rehman Mashwani (Horticulture, Environment, and Biotechnology, 2025)

High-performance disposable electrochemical sensors for creatinine derived from hollow CoNi-LDH@Creatinine-imprinted Poly(methacrylic acid) (i-PMA) composites - Muhammad Faheem; Zohaib Saddique; Toheed Akhter; Kun Wang; Jing Qian; Wuyan Gu; Adeel Afzal; Lingliang Long (Analytica Chimica Acta, 2025)

Role of the plant nurseries in spread of invasive alien plant species in Pakistan’s subtropical region; A threat for urban greening - Maria Shah; Shujaul Mulk Khan; Fazal Manan; Jawad Hussain; Zohaib U. Din; Imranullah Shah; Muhammad Arshad; Israr Ahmad (Urban Forestry & Urban Greening, 2025)

Exploring the therapeutic potential of Ixora extract: a comprehensive review of mediated studies - Rabiyah Nadeem; Muhammad Imran; Zohaib Saeed; Muhammad Pervaiz; Umer Younas (Advances in Traditional Medicine, 2025)

Retraction notice to “A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites” [Fuel 336 (2023) 126930] - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2025)

Retraction notice to Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review [FUEL][340][2023][127399] - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2025)

A comprehensive overview on the occurrence and removal of per- and polyfluoroalkyl substances through adsorption and biodegradation - Muhammad Zeeshan; Shamas Tabraiz; Safeerul Islam Hashmi; Arfa Iqbal; Daniel Dittmann; Zohaib Abbas; Cecilia L. MacLeod; Aki Sebastian Ruhl (Bioresource Technology Reports, 2025)

Utilizing contemporary machine learning techniques for determining soilcrete properties - Waleed Bin Inqiad; Muhammad Saud Khan; Zohaib Mehmood; Naseer Muhammad Khan; Muhammad Bilal; Mohammed Sazid; Saad S. Alarifi (Earth Science Informatics, 2025)
Soilcrete is an innovative construction material made by combining naturally occurring earth materials with cement. It can be effectively used in areas where other construction materials are not readily available due to financial or environmental reasons since soilcrete is made from readily available natural clay. It can also help to cut down the greenhouse gas emissions from the construction industry by encouraging the use of resources that are locally available. Thus, it is imperative to reliably predict different properties of soilcrete since the accurate determination of these properties is crucial for the widespread use of soilcrete materials. However, the laboratory determination of these properties is subjected to significant time and resource constraints. As a result, this research was undertaken to provide empirical prediction models for the density, shrinkage, and strain of soilcrete mixes using two machine learning algorithms: Gene Expression Programming (GEP) and Extreme Gradient Boosting (XGB). The analysis revealed that XGB-based predictions correlated more with real-life values than GEP having training $${\text{R}}^{2}=0.999$$ R 2 = 0.999 for both density and shrinkage prediction and $${\text{R}}^{2}=0.944$$ R 2 = 0.944 for strain prediction. Moreover, several explanatory analyses including individual conditional expectation (ICE) analysis and shapely analysis were done on the XGB model which showed that water-to-binder ratio, metakaolin content, and modulus of elasticity are some of the most important variables for forecasting soilcrete materials properties. Furthermore, an interactive graphical user interface (GUI) has been developed for effective utilization in civil engineering industry to forecast these properties of soilcrete materials.

Biovalorization of lignin-derived substrates to vanillylamine via a self-sufficient amino donor and cofactor recycling whole-cell platform - Fakhra Liaqat; Mahammed Ilyas Khazi; Taolin Ji; Nouman Liaqat; Yilin Le; Khalid A. Al-Ghanim; Muhammad Zohaib Nawaz; Damià Barceló; Daochen Zhu (Environmental Research, 2024)

Elucidating the bioremediation potential of laccase and peroxidase enzymes from Bacillus ligniniphilus L1 in antibiotic degradation: A computationally guided study - Muhammad Zohaib Nawaz; Hafiz Rameez Khalid; Muhammad Usman Mirza; Lingxia Xu; Syed Zeeshan Haider; Khalid A. Al-Ghanim; Damià Barceló; Daochen Zhu (Bioresource Technology, 2024)

Use of Metallic Nanoparticles Against Eimeria—the Coccidiosis-Causing Agents: A Comprehensive Review - Sahar Mustafa; Rao Zahid Abbas; Zohaib Saeed; Narjes Baazaoui; Arslan Muhammad Ali Khan (Biological Trace Element Research, 2024)

Appraisal of potentially toxic metals contamination in protein supplements for muscle growth: A chemometric approach and associated human health risks - Misbah Irshad; Mahmood Ahmed; Muhammad Ramzan; Mehreen Fatima; Fatima Aftab; Mudassar Sanaullah; Shaista Qamar; Zohaib Iftikhar; Tanveer A. Wani; Seema Zargar (Journal of Trace Elements in Medicine and Biology, 2024)

RETRACTED: Discovery of putative inhibitors of human Pkd1 enzyme: Molecular docking, dynamics and simulation, QSAR, and MM/GBSA - Muhammad Zohaib Nawaz; Hafiz Rameez Khalid; Sabeen Shahbaz; Khalid A. Al-Ghanim; Arivalagan Pugazhendhi; Daochen Zhu (Environmental Research, 2024)

Antioxidative enzymes, phytochemicals and proximate components in jujube fruit (Ziziphus mauritiana L.) with respect to genotypes and harvest maturity - Zohaib Asghar; Muhammad Amin; Sami Ullah; Hamad Hassan; Umm-e Habiba; Kashif Razzaq; Ishtiaq Ahmad Rajwana; Gulzar Akhtar; Hafiz Nazar Faried; Muhammad Aiyub; Shafa Nayab; Ambreen Naz; et al. (Food Bioscience, 2024)

A Comprehensive on Synthesis and Antimicrobial Evaluation of Substituted-Arylideneamino-5-(5-Chlorobenzofuran-2-yl)-1, 2, 4-Triazole-3-Thiol Derivatives/ Schiff Bases - Muhammad Rizwan; Sobia Noreen; Sadia Asim; Zohaib Liaqat; Hina Ibrahim; Rimsha Talib (Journal of Fluorescence, 2024)

Retraction Note: Investigation on the role of graphene-based composites for in photocatalytic degradation of phenol-based compounds in wastewater: a review - Shumila Shaheen; Rana Rashad Mahmood Khan; Awais Ahmad; Rafael Luque; Muhammad Pervaiz; Zohaib Saeed; Ahmad Adnan (Environmental Science and Pollution Research, 2024)

Ameliorative potential of eriocitrin against cadmium instigated hepatotoxicity in rats via regulating Nrf2/keap1 pathway - Muhammad Faisal Hayat; Muhammad Zohaib; Muhammad Umar Ijaz; Moazama Batool; Asma Ashraf; Bader O. Almutairi; Usman Atique (Journal of Trace Elements in Medicine and Biology, 2024)

Green synthesis, properties, and biomedical potential of gold nanoparticles: A comprehensive review - Zain Fatima; Ramsha Saleem; Rana Rashad Mahmood Khan; Maira Liaqat; Muhammad Pervaiz; Zohaib Saeed; Gulzar Muhammad; Muhammad Amin; Shahzad Rasheed (Biocatalysis and Agricultural Biotechnology, 2024)

Interactive impacts of photoaged micro(nano)plastics and co-occurring chemicals in the environment - Muhammad Junaid; Naima Hamid; Shulin Liu; Zohaib Abbas; Muhammad Imran; Muhammad Rizwan Haider; Bin Wang; Guanglong Chen; Hudda Khaleeq Khan; Qiang Yue; Nan Xu; Jun Wang (Science of The Total Environment, 2024)

Plant-mediated green synthesis of silver nanoparticles: Synthesis, characterization, biological applications, and toxicological considerations: A review - Zarfishan Zulfiqar; Rana Rashad Mahmood Khan; Muhammad Summer; Zohaib Saeed; Muhammad Pervaiz; Shahzad Rasheed; Behram Shehzad; Fatima Kabir; Saira Ishaq (Biocatalysis and Agricultural Biotechnology, 2024)

RNA based gene silencing modalities to control insect and fungal plant pests – Challenges and future prospects - Muhammad Waqas Choudry; Pashma Nawaz; Neelam Jahan; Rabia Riaz; Bilal Ahmed; Muhammad Hassan Raza; Zohaib Fayyaz; Kausar Malik; Samia Afzal (Physiological and Molecular Plant Pathology, 2024)

Correction to: Differential responses of Brassica napus cultivars to dual effects of magnesium oxide nanoparticles - Sharafat Ali; Zaid Ulhassan; Skhawat Ali; Zohaib Kaleem; Muhammad Arslan Yousaf; Mohamed S. Sheteiwy; Shafaqat Ali; Muhammad Waseem; Sanaullah Jalil; Jian Wang; Weijun Zhou (Environmental Science and Pollution Research, 2024)

Differential responses of Brassica napus cultivars to dual effects of magnesium oxide nanoparticles - Sharafat Ali; Zaid Ulhassan; Skhawat Ali; Zohaib Kaleem; Muhammad Arslan Yousaf; Mohamed S. Sheteiwy; Shafaqat Ali; Muhammad Waseem; Sanaullah Jalil; Jian Wang; Weijun Zhou (Environmental Science and Pollution Research, 2024)

Advanced nanomaterials and metal-organic frameworks for catalytic bio-diesel production from microalgal lipids – A review - Zohaib Saddique; Muhammad Imran; Shoomaila Latif; Ayesha Javaid; Shahid Nawaz; Nemira Zilinskaite; Marcelo Franco; Ausra Baradoke; Ewa Wojciechowska; Grzegorz Boczkaj (Journal of Environmental Management, 2024)

Synthesis of novel metal silica nanoparticles exhibiting antimicrobial potential and applications to combat periodontitis - Muhammad Zohaib Nawaz; Huda Ahmed Alghamdi; Mehvish Zahoor; Fizzah Rashid; Atheer Ahmed Alshahrani; Nuha S. Alghamdi; Arivalagan Pugazhendhi; Daochen Zhu (Environmental Research, 2024)

Genomic and biotechnological potential of a novel oil-degrading strain Enterobacter kobei DH7 isolated from petroleum-contaminated soil - Muhammad Zohaib Nawaz; Chunyan Xu; Majjid A. Qaria; Syed Zeeshan Haider; Hafiz Rameez Khalid; Huda Ahmed Alghamdi; Iqrar Ahmad Khan; Daochen Zhu (Chemosphere, 2023)

A comprehensive study of the sources, extraction methods and structures of the Saponin compounds for its antidiabetic activity - Muhammad Umair Afzal; Muhammad Pervaiz; Anam Ejaz; Eisha Bajwa; Sadaf Naz; Zohaib Saeed; Sami Ullah; Syeda Shaista Gillani; Rana Rashad Mehmood Kan; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Metagenomic investigations on antibiotic resistance and microbial virulence in oil-polluted soils from China - Majjid A. Qaria; Chunyan Xu; Arif Hussain; Muhammad Zohaib Nawaz; Daochen Zhu (Environmental Science and Pollution Research, 2023)

Hydrothermal synthesis of V2O5/TiO2 decorated graphitic carbon nitride nanocomposite for biomolecule oxidation inhibition and dye degradation applications - Muhammad Waseem; Awais Ahmad; Muhammad Sagir; Umer Younas; Zohaib Saeed; Muhammad Pervaiz; Faisal Ali; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Rama Rao Karri (Environmental Research, 2023)

“Garlic and ginger extracts mediated green synthesis of silver and gold nanoparticles: A review on recent advancements and prospective applications’’ - Zohaib Saeed; Muhammad Pervaiz; Anam Ejaz; Shah Hussain; Shumila Shaheen; Behram Shehzad; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Adverse multigeneration combined impacts of micro(nano)plastics and emerging pollutants in the aquatic environment - Muhammad Junaid; Junaid Ali Siddiqui; Shulin Liu; Ruijie Lan; Zohaib Abbas; Guanglong Chen; Jun Wang (Science of The Total Environment, 2023)

Bio-fabricated bismuth-based materials for removal of emerging environmental contaminants from wastewater - Zohaib Saddique; Muhammad Imran; Ayesha Javaid; Shoomaila Latif; Tak H. Kim; Marcin Janczarek; Muhammad Bilal; Teofil Jesionowski (Environmental Research, 2023)

RETRACTED: Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2023)

Precise geopressure predictions in active foreland basins: An application of deep feedforward neural networks - Muhammad Raiees Amjad; Muhammad Zafar; Muhammad Bilal Malik; Zohaib Naseer (Journal of Asian Earth Sciences, 2023)

RETRACTED: A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2023)

Linking environmental corporate social responsibility to firm performance: The role of partnership restructure - Zohaib Hussain Makhdoom; Yongqiang Gao; Xi Song; Wali Muhammad Khoso; Zulfiqar Ali Baloch (Environmental Science and Pollution Research, 2023)

A review of potential antibacterial activities of nisin against Listeria monocytogenes: the combined use of nisin shows more advantages than single use - Mengjie Wu; Yue Ma; Xin Dou; Muhammad Zohaib Aslam; Yangtai Liu; Xuejuan Xia; Shuo Yang; Xiang Wang; Xiaojie Qin; Takashi Hirata; Qingli Dong; Zhuosi Li (Food Research International, 2023)

Green synthesis of graphene-based metal nanocomposite for electro and photocatalytic activity; recent advancement and future prospective - Shumila Shaheen; Zohaib Saeed; Awais Ahmad; Muhammad Pervaiz; Umer Younas; Rana Rashad Mahmood Khan; Rafael Luque; Saravanan Rajendran (Chemosphere, 2023)

Genomic insights into the metabolic potential of a novel lignin-degrading and polyhydroxyalkanoates producing bacterium Pseudomonas sp. Hu109A - Muhammad Zohaib Nawaz; Huarong Shang; Jianzhong Sun; Alei Geng; Sameh S. Ali; Daochen Zhu (Chemosphere, 2023)

Effect of early feeding of L-arginine and L-threonine on hatchability and post-hatch performance of broiler chicken - Fazul Nabi; Muhammad Asif Arain; Zohaib Ahmed Bhutto; Qurban Ali Shah; Nasrullah Bangulzai; Nisar Ahmed Ujjan; Sarfaraz Ali Fazlani (Tropical Animal Health and Production, 2022)

Biological and Photocatalytic Degradation of Congo Red, a Diazo Sulfonated Substituted Dye: a Review - Rana Rashad Mahmood Khan; Hoorish Qamar; Ayesha Hameed; Aqmar ur Rehman; Muhammad Pervaiz; Zohaib Saeed; Aqib Adnan; Ayoub Rashid Ch (Water, Air, & Soil Pollution, 2022)

RETRACTED ARTICLE: Investigation on the role of graphene-based composites for in photocatalytic degradation of phenol-based compounds in wastewater: a review - Shumila Shaheen; Rana Rashad Mahmood Khan; Awais Ahmad; Rafael Luque; Muhammad Pervaiz; Zohaib Saeed; Ahmad Adnan (Environmental Science and Pollution Research, 2022)

Meta-omics approaches reveal unique small RNAs exhibited by the uncultured microorganisms dwelling deep-sea hydrothermal sediment in Guaymas Basin - Muhammad Zohaib Nawaz; Fengping Wang (Archives of Microbiology, 2022)

Microbial diversity and community structure in deep-sea sediments of South Indian Ocean - Daochen Zhu; Sivasamy Sethupathy; Lu Gao; Muhammad Zohaib Nawaz; Weimin Zhang; Jianxiong Jiang; Jianzhong Sun (Environmental Science and Pollution Research, 2022)

Development of Genome-wide SSR Markers for Physical Map Construction with PCR-based Polymorphic SSRs in Jute (Corchorus Spp.) - Sylvain Niyitanga; Jiayu Yao; Aminu kurawa Ibrahim; Muhammad Zohaib Afzal; Siyuan Chen; Liwu Zhang (Tropical Plant Biology, 2022)

QTL Mapping and Expression Analysis of Candidate Genes for Salt and Drought Tolerance in Corchorus capsularis Seedlings - Aminu Kurawa Ibrahim; Yi Xu; Sylvain Niyitanga; Muhammad Zohaib Afzal; Lilan Zhang; Liemei Zhang; Jianmin Qi; Liwu Zhang (Tropical Plant Biology, 2021)

Bio-purification of sugar industry wastewater and production of high-value industrial products with a zero-waste concept - Muhammad Zohaib Nawaz; Muhammad Bilal; Arslan Tariq; Hafiz M. N. Iqbal; Huda Ahmed Alghamdi; Hairong Cheng (Critical Reviews in Food Science and Nutrition, 2021)

Antiparkinsonian activity of Cucurbita pepo seeds along with possible underlying mechanism - Uzma Saleem; Aisha Shehzad; Shahid Shah; Zohaib Raza; Muhammad Ajmal Shah; Shabana Bibi; Zunera Chauhdary; Bashir Ahmad (Metabolic Brain Disease, 2021)

Dietary supplementations of methionine improve growth performances, innate immunity, digestive enzymes, and antioxidant activities of rohu (Labeo rohita) - Zohaib Noor; Mannal Noor; Syed Allauddin Khan; Waqar Younas; Daniya Ualiyeva; Zaigham Hassan; Ali Muhammad Yousafzai (Fish Physiology and Biochemistry, 2021)

Genomes of Diverse Isolates of Prochlorococcus High-Light-Adapted Clade II in the Western Pacific Ocean - Wei Yan; Xuejin Feng; Wei Zhang; Muhammad Zohaib Nawaz; Tingwei Luo; Rui Zhang; Nianzhi Jiao (Frontiers in Marine Science, 2021)

Mechanisms and Signaling Pathways of Salt Tolerance in Crops: Understanding from the Transgenic Plants - Muhammad Zohaib Afzal; Qi Jia; Aminu Kurawa Ibrahim; Sylvain Niyitanga; Liwu Zhang (Tropical Plant Biology, 2020)

Interactive role of zinc and iron lysine on Spinacia oleracea L. growth, photosynthesis and antioxidant capacity irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Hamzah Saleem; Mohsin Ali; Muhammad Riaz; Sehar Javed; Anam Sehar; Zohaib Abbas; Muhammad Rizwan; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni (Physiology and Molecular Biology of Plants, 2020)

Principles and approaches of association mapping in plant breeding - Aminu Kurawa Ibrahim; Liwu Zhang; Sylvain Niyitanga; Muhammad Zohaib Afzal; Yi Xu; Lilan Zhang; Liemei Zhang; Jianmin Qi (Tropical Plant Biology, 2020)

First report of cucurbit aphid borne yellows virus (CABYV) infecting melon in Pakistan - Muhammad Ahsan; Muhammad Ashfaq; Tariq Mukhtar; Nadeem Akhtar Abbasi; Zohaib Asad (Journal of Plant Pathology, 2020)

Role of Bioactive Peptides in Reducing the Severity of Hypertension with the Inhibition of ACE - Muhammad Zohaib Aslam; Muhammd Shoaib Aslam; Shumaila Firdos; Ghulam Ghous; Gulistan Firdos; Zhao Hongfei; Zhang Bolin (International Journal of Peptide Research and Therapeutics, 2019)

Peptidomic Analysis of ACE Inhibitory Peptides Extracted from Fermented Goat Milk - Muhammad Zohaib Aslam; Sana Shoukat; Zhao Hongfei; Zhang Bolin (International Journal of Peptide Research and Therapeutics, 2019)

Zinc-lysine prevents chromium-induced morphological, photosynthetic, and oxidative alterations in spinach irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Rizwan; Firdaus-e- Bareen; Zohaib Abbas; Syed Asad Hussain Bukhari; Leonard Wijaya; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Spatial disaggregation of ASCAT soil moisture under all sky condition using support vector machine - Seongkyun Kim; Jaehwan Jeong; Muhammad Zohaib; Minha Choi (Stochastic Environmental Research and Risk Assessment, 2018)

Yucca schidigera can mitigate ammonia emissions from manure and promote poultry health and production - Muhammad Saeed; Muhammad Asif Arain; Muhammad Naveed; Mahmoud Alagawany; Mohamed Ezzat Abd El-Hack; Zohaib Ahmed Bhutto; Marek Bednarczyk; Mohib Ullah Kakar; Mervat Abdel-Latif; Sun Chao (Environmental Science and Pollution Research, 2018)

Terminal drought and seed priming improves drought tolerance in wheat - Tahira Tabassum; Muhammad Farooq; Riaz Ahmad; Ali Zohaib; Abdul Wahid; Muhammad Shahid (Physiology and Molecular Biology of Plants, 2018)

A critical review of mechanisms involved in the adsorption of organic and inorganic contaminants through biochar - Zohaib Abbas; Shafaqat Ali; Muhammad Rizwan; Ihsan Elahi Zaheer; Afifa Malik; Muhammad Ahsan Riaz; Muhammad Rizwan Shahid; Muhammad Zia ur Rehman; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Regenerative Potential of Platelet Rich Fibrin (PRF) for Curing Intrabony Periodontal Defects: A Systematic Review of Clinical Studies - Shariq Najeeb; Zohaib Khurshid; Muhammad Atif Saleem Agwan; Shazia Akhbar Ansari; Muhammad Sohail Zafar; Jukka Pekka Matinlinna (Tissue Engineering and Regenerative Medicine, 2017)

Oral tissue engineering progress and challenges - Muhammad Sohail Zafar; Zohaib Khurshid; Khalid Almas (Tissue Engineering and Regenerative Medicine, 2015)